(untitled) (INNOVATIVE ECONOMY, 2020)
Diuk A.A. CONCEPTUAL ASPECTS OF FORMATION OF VILLAGE-PRESERVING MODEL OF MANAGEMENT ON THE BASIS OF SOCIALIZATION OF ENTREPRENEURSHIP Purpose. The aim of the article is deepening of theoretical and methodical bases of formation of village-preserving model of managing on the bases of socialization of entrepreneurship with the definition of the special significance of social entrepreneurial formations. Methodology of research. The theoretical and methodological basis of the study are the key provisions, principles and methods of modern business theory, social aspects of management and the concept of sustainable development of social economic systems, including the socialization of entrepreneurial activity with the peculiarities of agriculture. The results of the study are based on the use of such methods and approaches as: abstract and logical analysis – to determine the principles of socialization of entrepreneurial management, taking into account the theoretical foundations of the role of enterprises in the rural development system; generalization and systematization – with the conceptual substantiation of the advantages of the village-preserving model of management, as well as the characterization of the role of socialization of agricultural entrepreneurship for the activation of the functions of village-saving; systematic approach – to substantiate the scientific vision of the relationship between the principles of formation of a village-preserving model of management due to the factor of socialization of entrepreneurship with the UN Sustainable Development Goals until 2030. Findings. Theoretical provisions of the formation of the system of management in the countryside in terms of conceptual positioning of the essence of the village-preserving model on the basis of socialization of entrepreneurship are revealed. The theoretical and methodological characteristics of the unity of economic and social principles in ensuring the criteria of rural conservation on the basis of sustainability are determined. The methodical estimation of factors of maintenance of functioning of the modern agricultural enterprises with a projection on conditions of achievement of village-preserving social effect for development of territories is carried out. The general priorities of the state policy necessary for achievement which will promote realization of village-preserving model of managing, socialization of business with a projection on sustainable development are characterized. Originality. The conceptual aspects and principles of forming a village-preserving model of management, based on the socialization of entrepreneurship, are further developed. Practical value. The results of the conducted study can be the basis for further research on the development of strategy and substantiated of the principles of public policy in the field of sustainable development of villages, rural areas and the development of incentives to strengthen the social orientation of entrepreneurship. Key words: entrepreneurship, management, village, rural territories, village-preserving model, socialization, sustainable development.